Tingginya Angka Kriminalitas Akibat Terkikisnya Nilai Moral Generasi Penerus Bangsa - Fadly Mulyana Akbar; Wati Rohmawati; Wilda Rahayu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
High crime rates can have a negative impact on society's moral values. Crime can create insecurity, distrust and worry in society, which can undermine moral values. Apart from that, crime can also create damaging social norms. However, it is important to remember that the relationship between crime and moral values ​​is complex, and many other factors also play a role in shaping a society's moral values. This research uses a qualitative approach, namely natural, reasonable and what is, while the method used is descriptive analysis. Based on the research results, it can be concluded that there is a need for solutions to overcome increasingly high levels of criminality from various domains, especially from the legal and educational domains to improve moral values ​​and maintain healthy social integrity.